SARS-CoV-2 and Other Coronaviruses in Rats, Berlin, Germany, 2023 - Kerstin Wernike; Calvin Mehl; Andrea Aebischer; Lorenz Ulrich; Mario Heising; Rainer G. Ulrich; Martin Beer (Emerging Infectious Diseases)
We tested 130 rats captured in Berlin for coronaviruses. SARS-CoV-2 antibodies were detected in 1 rat, but all animals were negative by reverse transcription PCR, suggesting SARS-CoV-2 was not circulating in the rat population. However, alphacoronaviruses were found. Monitoring rodent populations helps to determine coronavirus occurrence, transmission, and zoonotic potential.